DNA ligases in the repair and replication of DNA - Timson, David J; Singleton, Martin R; Wigley, Dale B (Mutation research, 2000)
DNA ligases are critical enzymes of DNA metabolism. The reaction they catalyse (the joining of nicked DNA) is required in DNA replication and in DNA repair pathways that require the re-synthesis of DNA. Most organisms express DNA ligases powered by ATP, but eubacteria appear to be unique in having ligases driven by NAD+. Interestingly, despite protein sequence and biochemical differences between the two classes of ligase, the structure of the adenylation domain is remarkably similar. Higher organisms express a variety of different ligases, which appear to be targetted to specific functions. DNA ligase I is required for Okazaki fragment joining and some repair pathways; DNA ligase II appears to be a degradation product of ligase III; DNA ligase III has several isoforms, which are involved in repair and recombination and DNA ligase IV is necessary for V(D)J recombination and non-homologous end-joining. Sequence and structural analysis of DNA ligases has shown that these enzymes are built around a common catalytic core, which is likely to be similar in three-dimensional structure to that of T7-bacteriophage ligase. The differences between the various ligases are likely to be mediated by regions outside of this common core, the structures of which are not known. Therefore, the determination of these structures, along with the structures of ligases bound to substrate DNAs and partner proteins ought to be seen as a priority.